The creative processes in the cities: the case of Turkish literature - Stone, Leonard (Creativity Studies, 2025)
Utilizing a four-stage model of the creative process, this article explores the creative process of experiencing and representing the city in a selection of modern Turkish literature and illuminates how the creative process aligns with and informs writings on the Turkish city. The analysis is focused on the inspiration, dreaming, reflecting, and imagining procedures of the creative process incumbent upon writing the Turkish city; concepts that condition stages of creativity. This paper’s approach is in significant part a response to the theoretical problem of how the author situates the Turkish city, particularly regarding the capital Ankara, that is understood in the context of singularity and Istanbul, that is situated within a multiplicity of realities. This Ankara–Istanbul relationship is further referenced in the context of a discourse that is centered on the novel idea of an intersection of four tracts or a double chiasm. Several writers are referenced, especially the Turkish authors Ahmet Hamdi Tanpınar, Elif Shafak, and Orhan Pamuk.